Regio- and Stereoselective Copper-Catalyzed Ring Opening of Diheterobicyclic Alkenes with Grignard Reagents - Crotti, Stefano; Di Bussolo, Valeria; Pineschi, Mauro (Synthesis, 2012)
The ring opening of bicyclic hydrazines and bicyclic oxazines with organomagnesium reagents under the influence of copper catalysts allows functionalized cyclopentene and cyclohexene derivatives to be obtained. Whereas complete anti-stereoselective ring opening occurred in all cases, the regioselective outcome turned out to be highly dependent on the reaction conditions used.
Keywords: fused ring systems; cycloadducts; copper catalysis; Grignard reagents; regioselectivity; stereoselectivity